2022
DOI: 10.2217/fca-2022-0057
|View full text |Cite
|
Sign up to set email alerts
|

2D speckle-tracking Echocardiography As a Prognostic Imaging Modality for COVID-19 Adverse Outcomes

Abstract: Aim: 2D speckle-tracking echocardiography (2D-STE) has been used to assess cardiac recovery during the COVID-19 patient follow-ups within the pandemic. The novel role of STE in predicting adverse outcomes of COVID-19 has received attention due to its high sensitivity in identifying subclinical myocardial dysfunction. We reviewed the studies on using 2D-STE to assess COVID-19 prognosis. Methods: a literature search was conducted on PubMed and Scopus for eligible articles, 24 of which discussed using prognostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…2D-STE is a new technology which allows the observation of the entire complex motion of the myocardium in terms of torsion, shortening and thickening and other complex motion processes, and the various strain indicators it detects, providing a unique quantitative evaluation of cardiac function [21] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2D-STE is a new technology which allows the observation of the entire complex motion of the myocardium in terms of torsion, shortening and thickening and other complex motion processes, and the various strain indicators it detects, providing a unique quantitative evaluation of cardiac function [21] .…”
Section: Discussionmentioning
confidence: 99%
“…2D-STE has been recognized to overcome the weaknesses of conventional methods in recent years [9] . The longitudinal myocardium dominates the myocardial bers that make up the right ventricle, therefore monitoring the motion of the longitudinal myocardium is a valid approach to assess functional changes in the right ventricle.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest that the two-dimensional speckle tracking technique, based on two-dimensional grayscale imaging, selects a series of regions of interest from myocardial tissue and automatically tracks the position and motion of noisy spots in said regions of interest frame by frame according to tissue grayscale and heart rate cycle, thereby obtaining the strain rate and rotation angle of myocardial tissue motion independent of the direction of the acoustic beam and the angle between wall motion and overall cardiac motion. It provides a more objective method for evaluating myocardial function and more accurately reflects ventricular systolic and diastolic function by sensitively identifying abnormal myocardial segmental motion [9,15] . It is an echocardiographic technique used for deformation analysis of two-dimensional myocardial motion images, where individual "echo points" in the myocardial tissue are formed by reflection and scattering of small structures in the two-dimensional grayscale image below the incident echocardiographic wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…In a prospective study involving 100 patients hospitalized for COVID-19 who had TTE, the most common abnormality was RV dilatation and/or dysfunction, followed by LV diastolic dysfunction [34]. LV contractility [ejection fraction (EF)] remained normal in 90% of examined.…”
Section: Covid-19 Image On Echocardiographymentioning
confidence: 99%
“…There are studies aimed at an estimation of the prevalence of main imagined symptoms in patients with COVID-19. For example, Szekely et al [34] show that the most common echocardiographic sign observed in COVID-19 patients was RV dilation with or without dysfunction, which affected 39 patients out of 100 included in the study, followed by left ventricular diastolic dysfunction observed in 19 patients. However, the data concerning the sensitivity and specificity of imaging signs in COVID-19 patients are so far sparse.…”
Section: > 75% Involvementmentioning
confidence: 99%